Two new species and new records of Muscidae (Diptera) from Wrangel Island, Russia - Sorokina, Vera S. (Zootaxa, 2012)
Two new species in the genera Spilogona Schnabl and Coenosia Meigen are described from Wrangel Island (Spilogonakhrulevae sp. nov. and Coenosia wrangelensis sp. nov.). Their differences from closely related species are shown by theirinclusion in keys to these genera. Coenosia sibirica Hennig is newly recorded from the Russian Arctic. The male terminalia of all species are figured.